2017
DOI: 10.14348/molcells.2017.2204
|View full text |Cite
|
Sign up to set email alerts
|

Alu-Derived Alternative Splicing Events Specific to Macaca Lineages in CTSF Gene

Abstract: Cathepsin F, which is encoded by CTSF, is a cysteine proteinase ubiquitously expressed in several tissues. In a previous study, novel transcripts of the CTSF gene were identified in the crab-eating monkey deriving from the integration of an Alu element–AluYRa1. The occurrence of AluYRa1-derived alternative transcripts and the mechanism of exonization events in the CTSF gene of human, rhesus monkey, and crab-eating monkey were investigated using PCR and reverse transcription PCR on the genomic DNA and cDNA isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Several disease-causing mechanisms have been identified such as insertional mutagenesis and aberrant splicing [25, 28]. On the other hand, TEs can be advantageous elements that increase genomic diversity, and have a tremendous impact on evolution at the DNA and RNA levels by transduction-mediated gene formation, gene retrotransposition, alternative splicing, alternative polyadenylation, and the actions of alternative promoters, enhancers, and silencer elements [11, 18, 25]. In the present study, for the first time, we identified and validated that MIR_ Alu Sp combined sequences induced lineage-specific alternative splicing events and played an important role in diversifying BLOC1S2 gene transcripts, especially in the crab-eating monkey, rhesus monkey, and African green monkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several disease-causing mechanisms have been identified such as insertional mutagenesis and aberrant splicing [25, 28]. On the other hand, TEs can be advantageous elements that increase genomic diversity, and have a tremendous impact on evolution at the DNA and RNA levels by transduction-mediated gene formation, gene retrotransposition, alternative splicing, alternative polyadenylation, and the actions of alternative promoters, enhancers, and silencer elements [11, 18, 25]. In the present study, for the first time, we identified and validated that MIR_ Alu Sp combined sequences induced lineage-specific alternative splicing events and played an important role in diversifying BLOC1S2 gene transcripts, especially in the crab-eating monkey, rhesus monkey, and African green monkey.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Alu and MIR, which belong to the SINE family, are known to contribute to alternative splicing [16]. The Alu element, the most abundant TE in the human genome, is primate specific and composed of two similar monomers, the left and right arms, and these arms in the antisense orientation provide potential 5′- and 3′-splicing sites that can be recognized by the spliceosome [17, 18]. Moreover, a previous study has shown that Alu creates ~ 5% of the alternatively spliced exons in the human genome; thus, it is considered crucial for AS events [19].…”
Section: Introductionmentioning
confidence: 99%
“…This element is about 300 bases long, formed from two similar monomers, called "leftarm" and "right-arm" 18,21 . Antisense Alu in the genic region tends to provide potential splicing donor (GT) and acceptor (AG) sites, creating a new exon for the transcript 10,22 . This Alu-involved AS event accounts for ~ 5% of all internal alternative exons in the human genome 23 .…”
mentioning
confidence: 99%